2003
DOI: 10.2320/matertrans.44.539
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Voltage-Current Characteristics of Anodic Films Formed on Magnesium in Electrolytes Containing Fluoride

Abstract: Formation behavior of anodic oxide films on magnesium in various electrolytes including fluoride was investigated with attention to the effects of anodizing voltage, pH and aluminum content. In the range of formation voltage between 2 V and 100 V, porous film was formed in alkaline fluoride solution associated with high current density at around 5 V and at breakdown voltage. The critical voltage of breakdown to allow maximum current flow was approximately 60 V and relatively independent on substrate purity. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…[6] Ono et al reported similar breakdown potentials for various fluoride containing solutions. [7,8] They found that except at around 5V and breakdown voltages, a barrier type film or a semi-barrier film was formed in the alkaline fluoride solution. Above the breakdown potential, porous films were formed.…”
Section: Film Formation -Anodizing Behaviourmentioning
confidence: 99%
See 3 more Smart Citations
“…[6] Ono et al reported similar breakdown potentials for various fluoride containing solutions. [7,8] They found that except at around 5V and breakdown voltages, a barrier type film or a semi-barrier film was formed in the alkaline fluoride solution. Above the breakdown potential, porous films were formed.…”
Section: Film Formation -Anodizing Behaviourmentioning
confidence: 99%
“…The atomic ratio of aluminium to magnesium increased with increasing voltage to attain 0.42 at 80 V and crystalline MgAl 2 O 4 and MgO were found in the film. [8] The anodic behaviour of Mg-Al-Zn alloy (AZ91D) under low potential in 3 M KOH solutions was studied with and without addition of 0.5-5 M Na 2 SiO 3 . [9] Anodic films incorporating silicon were formed during electrolysis, and the films formed under a constant potential of 4 V in 3 M KOH solution with Na 2 SiO 3 were uniform and thicker than the films formed without Na 2 SiO 3 .…”
Section: Film Formation -Anodizing Behaviourmentioning
confidence: 99%
See 2 more Smart Citations
“…5) Plasma electrolytic oxidation (PEO) has recently attracted attention to form ceramic-like coatings on aluminum, magnesium and titanium for corrosion and wear resistance. [6][7][8] Spark micro-discharge in PEO process modifies the structure, composition and morphology of the oxide layer; a thick, highly crystalline and melt-quenched high temperature oxide coating is formed by this process.…”
Section: Introductionmentioning
confidence: 99%